The Impact of Financial Education on Adolescents' Intertemporal Choices - Melanie Lührmann; Marta Serra-Garcia; Joachim Winter (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine the impact of a large high-school financial education program on the intertemporal choices of adolescents. We randomly assigned the program among a sample of almost 1,000 students and measured their intertemporal choices using an incentivized experiment. While intertemporal choices in the control group exhibit significant present bias, choices among treated students are time consistent on average. We structurally estimate individual preference parameters, explicitly allowing choices to be stochastic. Participation in the program increases time consistency and decreases error rates. These findings suggest that financial education can have significant effects on intertemporal choice already at a young age.
Keywords: D14; D91; C93; 330; intertemporal choice; financial education; experiment